ANALISIS MANAJEMEN KELAS RENDAH DITINJAU DARI STANDAR SARANA DAN PRASARANA DI SDIT AR RISALAH TABALONG - Sudarjat Sudarjat; Slamet Widodo (LPPM Universitas Bina Bangsa, 2022)
Classroom management is a very urgent activity for education. The class management function says that the function of facilities and infrastructure is to develop and seek the potential of students, both from intellectual, physical, and spiritual aspects. However, problems arise in the discomfort of students in the classroom. This is because the facilities and infrastructure, especially the facilities and infrastructure in the classroom, have not met the standards. Based on these problems, researchers try to provide advice to schools to streamline and use existing facilities as optimally as possible based on the function of facilities and infrastructure. This study aims to determine classroom management in terms of facilities and infrastructure as well as the management of curriculum and learning activities contained in SDIT AR RISALAH Tabalong. This research uses qualitative descriptive method. Based on the results of data analysis obtained from observations, interviews and documentation, results were obtained for standards of facilities and infrastructure that did not meet building floor standards and the results of curriculum management and learning activities were met